Reexamining the categorical exclusion of pediatric participants from controlled human infection trials. (26th July 2020) - Murphy, Sean C.; Duenas, Devan M.; Richie, Thomas L.; Shah, Seema K.
ABSTRACT: Controlled human infection (CHI) models have been developed for numerous pathogens in order to better understand disease processes and accelerate drug and vaccine testing. In the past, some researchers conducted highly controversial CHIs with vulnerable populations, including children. Ethical frameworks for CHIs now recommend vulnerable populations be excluded because they cannot consent to high risk research. In this paper we argue that CHI studies span a wide spectrum of benefit and risk, and that some CHI studies may involve minimal risk. The categorical exclusion of children from CHIs therefore departs from the standard approach to evaluating research risks, as international regulations and ethical guidance for pediatric research generally permit non‐beneficial research with low risks. The paradigm in research ethics has also shifted from focusing on protecting vulnerable participants to recognizing that inclusion can be important as a matter of justice, providing new reasons to question this default exclusion of children from CHIs. Recognizing that pediatric CHIs can raise complex ethical issues and are easy to sensationalize in ways that may threaten the public's trust in research and sponsor institutions, we conclude by describing additional complexities that must be addressed before pediatric CHIs beyond licensed vaccine studies might be ethically acceptable.